Imatinib induced bone marrow hypoplasia in a case of chronic myelogenous leukemia - Kausar, Mehlam; Karpurmath, Shashidhar V.; Nandennavar, Manjunath I.; Jacob, Roshan K.; Angadi, Veerendra; Sekar, Annalakshmi (International Journal of Research in Medical Sciences, 2019)
Imatinib mesylate a tyrosine kinase inhibitor first introduced for the treatment of chronic myelogenous leukaemia (CML) since May 2001, has revolutionised the management of CML. Imatinib is the first choice of treatment for patient with CML chronic phase (CML-CP) and generally the drug is well tolerated. A number of haematological and non-haematological side effects are associated with it. Bone marrow hypoplasia is one of the rare side effects noted with imatinib. We report a case of 46-year-old male a case of CML-CP who developed bone marrow hypoplasia following treatment with imatinib for a period of six months with bone marrow biopsy showing decreased cellularity.